Warriors. A thief in ThunderClan - Hunter, Erin (Hunter, Erin. Warriors (Graphic novel), 2023)
After recovering from the dog attack she survived as an apprentice, Brightheart is once again a warrior of ThunderClan. But moons of battle and betrayal have left her with lingering suspicions about where her Clanmates' loyalties lie. So when fresh-kill starts going missing from camp, she fears the worst. Alongside her mate Cloudtail, Brightheart decides to investigate without alerting the other warriors. But as she struggles to track down the culprit, she'll have to take a leap of faith about who she can trust--and remember what it means to be part of a Clan.